Green tea consumption and incidence of cardiovascular disease in type 2 diabetic patients with overweight/obesity: a community-based cohort study - Bingyue Liu; Shujun Gu; Jin Zhang; Hui Zhou; Jian Su; Sudan Wang; Qian Sun; Zhengyuan Zhou; Jinyi Zhou; Chen Dong (BMC, 2024)
Abstract Background Green tea has been reported to be potentially protective against the development of cardiovascular disease (CVD). This study aimed to investigate the association between green tea consumption and incident CVD in type 2 diabetes (T2D) patients with overweight/obesity. Methods A total of 4756 Chinese overweight/obese T2D patients were recruited and followed up for 6.27 years. Information on green tea consumption was collected at baseline using interviewer-administered questionnaires. Hazard ratios (HRs) and 95% confidence intervals (CIs) for incident CVD according to green tea consumption were estimated using the Cox proportional hazards model. Results Compared with non-habitual consumers, participants who consumed > 5 g/day of green tea leaves reduced the risk of CVD by 29% (95%CI: 0.55-0.92), stroke by 30% (95%CI: 0.51-0.95) and coronary heart disease (CHD) by 40% (95%CI: 0.40-0.89). Similarly, participants who consumed green tea for ≥ 40 years reduced the risk of CVD by 31% (95%CI: 0.54-0.88), stroke by 33% (95%CI: 0.50-0.90) and CHD by 39% (95%CI: 0.42-0.88). Among participants with < 5-year history of T2D, > 5 g/day of tea leaves and > 40 years of tea consumption were associated with 59% (95%CI: 0.23-0.72) and 57% (95%CI: 0.26-0.74) reduced risk of stroke, respectively. However, among participants with ≥ 5-year history of T2D, > 5 g/day of tea leaves and > 40 years of tea consumption were associated with a 50% (95%CI: 0.30-0.82) and 46% (95%CI: 0.35-0.85) reduced risk of CHD, respectively. Conclusions Green tea consumption is associated with reduced risk of CVD, stroke, and CHD in overweight/obese T2D patients.